Respuesta :

Answer:

[tex]v = \frac{32\pi}{3}[/tex]

or

[tex]v=33.52[/tex]

Step-by-step explanation:

Given

[tex]f(x) = 4x - x^2[/tex]

[tex]g(x) = x^2[/tex]

[tex][a,b] = [0,2][/tex]

Required

The volume of the solid formed

Rotating about the x-axis.

Using the washer method to calculate the volume, we have:

[tex]\int dv = \int\limit^b_a \pi(f(x)^2 - g(x)^2) dx[/tex]

Integrate

[tex]v = \int\limit^b_a \pi(f(x)^2 - g(x)^2)\ dx[/tex]

[tex]v = \pi \int\limit^b_a (f(x)^2 - g(x)^2)\ dx[/tex]

Substitute values for a, b, f(x) and g(x)

[tex]v = \pi \int\limit^2_0 ((4x - x^2)^2 - (x^2)^2)\ dx[/tex]

Evaluate the exponents

[tex]v = \pi \int\limit^2_0 (16x^2 - 4x^3 - 4x^3 + x^4 - x^4)\ dx[/tex]

Simplify like terms

[tex]v = \pi \int\limit^2_0 (16x^2 - 8x^3 )\ dx[/tex]

Factor out 8

[tex]v = 8\pi \int\limit^2_0 (2x^2 - x^3 )\ dx[/tex]

Integrate

[tex]v = 8\pi [ \frac{2x^{2+1}}{2+1} - \frac{x^{3+1}}{3+1} ]|\limit^2_0[/tex]

[tex]v = 8\pi [ \frac{2x^{3}}{3} - \frac{x^{4}}{4} ]|\limit^2_0[/tex]

Substitute 2 and 0 for x, respectively

[tex]v = 8\pi ([ \frac{2*2^{3}}{3} - \frac{2^{4}}{4} ] - [ \frac{2*0^{3}}{3} - \frac{0^{4}}{4} ])[/tex]

[tex]v = 8\pi ([ \frac{2*2^{3}}{3} - \frac{2^{4}}{4} ] - [ 0 - 0])[/tex]

[tex]v = 8\pi [ \frac{2*2^{3}}{3} - \frac{2^{4}}{4} ][/tex]

[tex]v = 8\pi [ \frac{16}{3} - \frac{16}{4} ][/tex]

Take LCM

[tex]v = 8\pi [ \frac{16*4- 16 * 3}{12}][/tex]

[tex]v = 8\pi [ \frac{64- 48}{12}][/tex]

[tex]v = 8\pi * \frac{16}{12}[/tex]

Simplify

[tex]v = 8\pi * \frac{4}{3}[/tex]

[tex]v = \frac{32\pi}{3}[/tex]

or

[tex]v=\frac{32}{3} * \frac{22}{7}[/tex]

[tex]v=\frac{32*22}{3*7}[/tex]

[tex]v=\frac{704}{21}[/tex]

[tex]v=33.52[/tex]